PENGARUH KURIKULUM MERDEKA PADA MATA PELAJARAN PAI TERHADAP AKHALAK SISWA DI SMP PGRI KASIHA BANTUL - Siti Fatimah (LPPM IAI Almuslim Aceh, 2024)
This study examines the impact of the independent curriculum in the Islamic Education (PAI) subject on students' morals at SMP PGRI Kasihan Bantul. There are three main issues investigated in this research. First, how the independent curriculum is implemented in the PAI subject at SMP PGRI Kasihan Bantul. Second, how the students' morals are at SMP PGRI Kasihan Bantul. Third, to what extent the independent curriculum in the PAI subject influences the students' morals at SMP PGRI Kasihan Bantul. The population of this study comprises 158 students from grades VII and VIII at SMP PGRI Kasihan Bantul. Considering the population exceeds 100, the researcher used random sampling with the Slovin formula, resulting in a sample of 61 students. The data collection techniques used are interviews, observations, questionnaires, and documentation. Data collection took place from January 29 to 30, 2024. The data analysis techniques used are descriptive analysis, prerequisite tests, and hypothesis testing. The results of this study indicate that the independent curriculum in the PAI subject at SMP PGRI Kasihan Bantul falls into the moderate category, and the students' morals are also in the moderate category. The influence of the independent curriculum in the PAI subject on students' morals is 27.5%, while 72.5% of moral development is influenced by other factors not examined in this study